Brontostoma lilloi Carpintero, 1980, a junior synonym of B. rubrovenosum (Stål, 1860) (Hemiptera: Heteroptera: Reduviidae) - Gil-Santana, Hélcio R.; Carpintero, Diego L. (Zootaxa, 2019)
There are 22 genera and more than 100 described species of Ectrichodiinae in the New World (Gil-Santana et al. 2015). Intraspecific variation in coloration and body size have been recorded in several species of the subfamily. These characteristics can occur in the same population or can suggest geographic variation of the same species (Wygodzinsky 1951, Dougherty 1995, Gil-Santana & Baena 2009, Gil-Santana et al. 2013). Sexual dimorphism is also common: females are almost always more or less larger than males, frequently have thicker fore femora and smaller eyes and ocelli (Dougherty 1995).